Evaluación de la significancia de los momentos de ubicación de coberturas plásticas en el porcentaje letal de malezas herbáceas del maíz en Moyobamba - Casique Gonzáles, Jon Harrinzon (2015)
The project was carried out in Moyobamba province, in the sector "Shica", on the right bank of the river Tonchima, during two phases, the fust of February to April 2014, the second from August to October 2014. The specific objectives were: find the significant moments in the plastic cover for the greatest percentage of lethal herbaceous weeds; analyze the relationship between the percentage of mortality of weeds and the temperature under the plastic sheeting, rainfall and the hours of sunshine. The wording of this problem is there significance between the moments of location of plastic mulch, in the percentage oflethal herbaceous weeds ofmaize?. The variables were: Moments of plastic sheeting (independent variable) and the percentage of lethal herbaceous weeds in the maize field ( dependent variable), taking the hypothesis to demonstrate, if we placed at different times the plastic cover on the ground with plantings of maize, then, we find significance in the percentage of lethal herbaceous weeds of maize. Among the treatments evaluated were, plastic located on the same day ofplanting (TI), Plastic located at 03 days after sowing (T2), Plastic located at 06 days after sowing (T3), Plastic located at 09 days after sowing (T4), Plastic located at 12 days after sowing (TS), more a witness without coverage (T6). In the present experiment, it was used the design of complete blocks at random (BCA) with three repetitions. The conclusions were: The significant moment oftransparent plastic location, between the months ofFebruary, March and April, in the rainy stage (stage 1), was 12 days after sowing ofmaize (TS); and between the months August, September and October ofthe year 2014, at the time less often rainy (Stage 11), went to the 06 days after sowing (T3), in both cases presented the 100% mortality ofweeds. When the T0 is incremented by 1 °C, the% ofmortality increases by 0.42 (b = 0.42), and 100% of factors that influence the % mortality of weeds, 16 % is due to the T0 under the plastic cover (r2= 0.16 y r = 0.42). Ifrainfall increases by one unit, the% mortality decreases in 0.017% (b = - 0.017), tbe precipitation influences a decrease of 58% ofthe mot1ality ofweeds (r = -0.76 y r2 = 0.58). The solar radiation has a direct influence for every hour of sun rose 0.02 % mortality of weeds, expressed in b = 0.02, with an r = 0.39 and r2 = 0.15 that indicates that 100% ofthe variations of the % mortality of weeds, 15 per cent was due to the hours of sunshine on the plastic cover. The moments of coverage have greater influence in the % of 1ethal weeds during the rainiest months, from February to April, reporting a correlation coefficient (r) equal to 0.7 and a regression coefficient (b) equal to O .3. However from August to October the regression coefficient (b) was equal to 0.06 and the correlation coefficient (r) equal to 0.2. Key words: plastic sheeting, lethal herbaceous weeds.